If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(m + -5) + 6(-3m + -6) = -15(m + 2) + -5 Reorder the terms: 4(-5 + m) + 6(-3m + -6) = -15(m + 2) + -5 (-5 * 4 + m * 4) + 6(-3m + -6) = -15(m + 2) + -5 (-20 + 4m) + 6(-3m + -6) = -15(m + 2) + -5 Reorder the terms: -20 + 4m + 6(-6 + -3m) = -15(m + 2) + -5 -20 + 4m + (-6 * 6 + -3m * 6) = -15(m + 2) + -5 -20 + 4m + (-36 + -18m) = -15(m + 2) + -5 Reorder the terms: -20 + -36 + 4m + -18m = -15(m + 2) + -5 Combine like terms: -20 + -36 = -56 -56 + 4m + -18m = -15(m + 2) + -5 Combine like terms: 4m + -18m = -14m -56 + -14m = -15(m + 2) + -5 Reorder the terms: -56 + -14m = -15(2 + m) + -5 -56 + -14m = (2 * -15 + m * -15) + -5 -56 + -14m = (-30 + -15m) + -5 Reorder the terms: -56 + -14m = -30 + -5 + -15m Combine like terms: -30 + -5 = -35 -56 + -14m = -35 + -15m Solving -56 + -14m = -35 + -15m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '15m' to each side of the equation. -56 + -14m + 15m = -35 + -15m + 15m Combine like terms: -14m + 15m = 1m -56 + 1m = -35 + -15m + 15m Combine like terms: -15m + 15m = 0 -56 + 1m = -35 + 0 -56 + 1m = -35 Add '56' to each side of the equation. -56 + 56 + 1m = -35 + 56 Combine like terms: -56 + 56 = 0 0 + 1m = -35 + 56 1m = -35 + 56 Combine like terms: -35 + 56 = 21 1m = 21 Divide each side by '1'. m = 21 Simplifying m = 21
| 1/5q=9-2/q | | 17+5x=8(x+1) | | 5-x/3= | | 220+1/2x-12x | | -12x+3=5x | | -44+3x-10=8-7x-2 | | 9z-1-3z=-4+6z+13 | | 7y-4y-13=43.49 | | x^2-4x-2y-1=0 | | x/(2x+3)=(x-1)/(2x) | | 98=7(x+8) | | 8a=0.32 | | 17-2x-7=2-2x | | 6-6x=6x-9x-9 | | x(x-1)=x(x+1) | | 60-8x=8x | | 11y-6y-13=55.90 | | 6-24x+36y=0 | | -25+3x=-2x | | 11x-9-5=10x-4+3x | | 4x+5x-42=70-5x | | 15x=4/10 | | (x-5)+17=-3 | | 2tsp=XmL | | 38-4x=12+9x | | 42-n=28 | | -11=3+7x | | b-3+4b=-7+4b | | 3/5+2x=2/5 | | 4(x+18)=-2(x-6) | | -11X+6Y=-13 | | 2w-15w-18=-83 |